Utilization of positive psychosocial strengths in adolescents’ career development during the transition from primary to secondary education - Αηδόνη, Μαρία; Αργυροπούλου, Κατερίνα (Education Sciences, 2021)
The transition from primary to secondary education requires flexible adaptation. The utilization of positive psychosocial strengths is an important mechanism for adapting management changes in adolescents’ educational process. This article presents the relationship between positive psychosocial strengths (hope and optimism) on issues of career development of students in the last grade of primary school. The results of the research showed that a positive attitude towards the future contributes effectively to the cultivation of self-perception, career exploration and the development of targeting skills in the management of students’ educational and professional course. The results are discussed in the context of career guidance, emphasizing the importance of its preventive, pedagogical and lifelong character.